TEOLOGI HASAN HANAFI DAN RELEVANSINYA DENGAN REVOLUSI INDUSTRI 4.0 - Muhammad Yuslih (Jurnal Keislaman, 2022)
A person's actions or behavior cannot be taken from the beliefs or theological schools he adheres to, because it will become the basic foundation in everyday life. This paper aims to reveal the theological ideas of Hasan Hanafi, who is one of the leading theologians or contemporary kalam, and how it relates to the industrial revolution 4.0. This type of research is included in the category of library research. The data obtained in this study were sourced from the results of reading and searching related to Hasan Hanafi's theological ideas and also the Industrial revolution 4.0 from various books, journals, the internet and other sources. The results of the research and reading of the researcher show that the industrial revolution 4.0 requires humans to take a role and present themselves, besides that the readiness of responsive and innovative human resources is an absolute requirement, and has extensive knowledge in facing the industrial revolution 4.0. In addition, humans must avoid all forms of behavior that damage or harm themselves, and strengthen brotherhood. All of these have relevance to the theological concepts initiated by Hasan Hanafi, namely Wujud (existent), Qhidam (formerly), Mukhalafatu Li Al-Hawadist (Different from Others) and Qiyam Binafsihi (Standing Alone), Baqa' (eternal), Wahdaniyyah (unity).